Seni Kaligrafi: Peran Dan Kontribusinya terhadap Peradaban Islam - Laily Fitriani (UIN Maulana Malik Ibrahim Malang, 2011)
Calligraphy, one of the Islamic arts, has gotten a great attention in Muslim community. Basically, calligraphy is artistic writings (khat) taken from Al Quran and it is named based on the place: Makki, Madani, Anbari and Baghdadi. By the time, names of (khat) shown, seems like Khufi, Mutsallats, Mudawwar, and some other types of writing. Calligraphy has a big role in developing Islamic civilization in the world. The influence of Islamic power expantions, Arabitation, the role of the King and social elites give motivation and facilitate the development of calligraphy and influent the development of science especially in Abbasiyah period. After the Abbasiyah period, the existence of calligraphy still was existing, developing and showing the phenomenal calligrafers like Ibnu Muqlah. Kaligrafi, salah satu seni Islam, mendapat perhatian besar dalam komunitas Muslim. Pada dasarnya, kaligrafi adalah tulisan artistik (khat) yang diambil dari Al Quran dan dinamai berdasarkan tempat: Makki, Madani, Anbari dan Baghdadi. Pada saat itu, nama (khat) yang ditampilkan, sepertinya Khufi, Mutsallats, Mudawwar, dan beberapa jenis tulisan lainnya. Kaligrafi memiliki peran besar dalam mengembangkan peradaban Islam di dunia. Pengaruh ekspedisi kekuatan Islam, Arabitasi, peran Raja dan elit sosial memberikan motivasi dan memudahkan pengembangan kaligrafi dan mempengaruhi perkembangan ilmu pengetahuan khususnya pada masa Abbasiyah. Setelah masa Abbasiyah, keberadaan kaligrafi masih ada, berkembang dan menunjukkan kaligrafi fenomenal seperti Ibnu Muqlah.